Pengembangan Instrumen Penilaian Keterampilan Berpikir Kritis Pada Materi Gelombang Cahaya Untuk Siswa SMA - Kumalasari, Siti Nurhaini; Putra, Ngurah Made Dharma (UPEJ Unnes Physics Education Journal, 2021)
This research aims to develop an instrument for assessing critical thinking skills on light wave topic which refers to Ennis's ten indicators of critical thinking. The type of the research is Research and Development (R&D) with ADDIE design. The data collection methods used were test, response questionnaire, and interviews. This research was conducted at SMAN 1 Jatisrono online using google form. A total of 20 essay questions were designed to be pre-trial tested in class XI MIPA 5 and produce ten appropriate essay questions then used for trial test in XI MIPA 1 and 2. The test instruments were declared worthy based on three categories, they’re expert judgment, reliability testing, and student responses. The percentage of eligibility of experts is 85.42%, it shows that the instrument is suitable for use. This instrument is declared reliable for use, with a reliability value of 0.71. The difficulty index of the test is on the medium and easy level with moderate discrimination index. The results of the critical thinking analysis show that as many as 40% of students have high critical thinking criteria. As many as 60% of students responded well to the test instrument.